2015
DOI: 10.1007/s11240-015-0811-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on the accumulation of indolizidine alkaloids in Securinega suffruticosa callus cultures

Abstract: In the presented work, plant growth regulators (PGRs) were tested for their influence on biomass growth and accumulation of therapeutically-relevant indolizidine alkaloids in Securinega suffruticosa (Phyllanthaceae) callus cultures. The study included 9 auxins [2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid, indole-3-acetic acid (IAA), 4-chlorophenoxyacetic acid, indole-3-butyric acid, 4-amino-3,5,6-trichloropicolinic acid, b-naphthoxyacetic acid, 1-naphthaleneacetic acid, indole-3-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…The callus cultures were successfully established from the root explants obtained from in vitro seedlings of P. multiflorum . Previous studies have demonstrated that auxins and cytokinins directly influence the biosynthesis of secondary metabolites in plant cell or tissue culture [18,19]. Appropriate concentration of the medium is a critical determinant for controlling callus growth and metabolite production.…”
Section: Resultsmentioning
confidence: 99%
“…The callus cultures were successfully established from the root explants obtained from in vitro seedlings of P. multiflorum . Previous studies have demonstrated that auxins and cytokinins directly influence the biosynthesis of secondary metabolites in plant cell or tissue culture [18,19]. Appropriate concentration of the medium is a critical determinant for controlling callus growth and metabolite production.…”
Section: Resultsmentioning
confidence: 99%
“…Basal medium and plant growth regulators (PGRs) play a significant role in tissue morphogenesis, differentiation and secondary metabolite production (Raj et al 2015). As most of the terpenoids and flavonoids were found in the licorice roots, the role of basal media composition and PGR effect on root tissue differentiation and secondary metabolite production was investigated in in vitro raised cultures of G. glabra.…”
Section: Effect Of Basal Media and Growth Regulators On Morphogenesismentioning
confidence: 99%
“…The varied chemical spectrum is probably due to PGR effect as the root explants were of same age and origin and were grown under similar in vitro conditions. Recent works of on Anacyclus pyrethrum (Singh et al 2015) and Securinega suffruticose (Raj et al 2015) have demonstrated the effect of PGR combinations on plant differentiation and secondary metabolite accumulation.…”
Section: Effect Of Basal Media and Growth Regulators On Morphogenesismentioning
confidence: 99%
“…Scientific data regarding securinega-type alkaloids in Phyllanthus species are limited and mostly relate to isolation methods (Babady et al 1996;Houghton et al 1996;Negi and Fakhir 1988). In the literature, there are described research concerning the influence of plant growth regulators on the accumulation of securinega-type alkaloids in in vitro conditions; however, none of these concern Phyllanthus species ( Raj et al 2015;Yuan et al 2007). In addition, the method for micropropagation of Phyllanthus species as a source of securinega-type alkaloids has not been provided yet.…”
Section: Introductionmentioning
confidence: 99%